2018 18th International Conference on Harmonics and Quality of Power (ICHQP) 2018
DOI: 10.1109/ichqp.2018.8378829
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of finite control set model predictive controlled active harmonic filter

Abstract: This paper presents a finite control set model predictive control (FCS-MPC) based shunt active harmonic filter (SAHF) for power quality improvement. A detailed mathematical model of a SAHF is considered and used with the FCS-MPC algorithm for future prediction. The reference currents required for harmonic mitigation and reactive power compensation are generated using p-q theory. The two step ahead reference values required for compensating calculation delay in the FCS-MPC algorithm are obtained by using vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Each method has its pros and cons, as presented in [11, 29, 31]. Moreover, several works have discussed the power converter controller, as presented in [2–4, 9, 20, 32]. The new control structure in this study is utilising the predictive control and compare it with a similar structure using the space vector control as explained in the previous section.…”
Section: Proposed Control Structure and System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each method has its pros and cons, as presented in [11, 29, 31]. Moreover, several works have discussed the power converter controller, as presented in [2–4, 9, 20, 32]. The new control structure in this study is utilising the predictive control and compare it with a similar structure using the space vector control as explained in the previous section.…”
Section: Proposed Control Structure and System Descriptionmentioning
confidence: 99%
“…It is worth noticing that in [1, 6, 7] it is shown that not all the control algorithms are working appropriately in the presence of a non‐ideal voltage. As discussed in [8–10], shunt APFs (SAPFs) are the most suitable to deal with harmonic current distortion as well as improving the total power factor performance by reducing the reactive power burden on the power system [11].…”
Section: Introductionmentioning
confidence: 99%